Hubungan Antara Pengaruh Normatif dan Niat Beli Pakaian Merek Luar Negeri: Kesadaran Merek, Kualitas, dan Nilai Emosi Sebagai Variabel Mediasi - Shannaz Nadya; Sabrina O Sihombing (Conference In Business, Accounting, And Management (CBAM), 2012)
Clothing is a primary need of man. Along with the times, the main function of clothing shifted. Clothes are not just a mere body cover but this time into a product category that represents the person. Therefore, more and more local brands and foreign brands in Indonesia. Many brand choices make the company needs to implement an effective marketing strategy in order to maintain its market. Companies need to know the factors that influence consumer purchase intention in order to formulate effective marketing strategies. Research on consumer purchase intention towards foreign apparel brands has been done in other countries. However, only few studies were developed in Indonesia. Therefore, this study aimed to examine the relationship normative influence, brand consciousness, perceived quality, emotional values on purchase intention. The data in this study were obtained by distributing questionnaires to the respondents. The selection of respondents using a non-probability judgmental sampling technique. Questionnaires were distributed to 226 respondents and as many as 200 questionnaires that can be used for further analysis. The data then was analyzed by using structural equation modeling approach. The analysis showed all hypotheses are supported. The study also provides implications for theoretical and managerial implications and suggestions for future research.Keywords: purchase intention, normative influence, brand consciousness, perceived quality, emotional values